Performance investigation of a kaplan hydraulic turbine draft tube using CFD techniques - Samaneh, Hajikhani; Amir, Raja; S. Mostafa, Hosseinalipour; Kamran, Mobini (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.